1992
DOI: 10.1159/000126167
|View full text |Cite
|
Sign up to set email alerts
|

Luteinizing Hormone Response to Oxytocin Is Steroid-Dependent

Abstract: Oxytocin-induced LH release from dispersed rat anterior pituitary cells in vitro was shown to be dependent on the steroidal environment. Preincubation of anterior pituitary cells with estradiol for 48 h enhanced the subsequent LH response to oxytocin (p < 0.001). Maximal sensitization was observed with estradiol at 1 nM. Release of LH induced by oxytocin was inhibited in the presence of progesterone or to a greater extent in the presence of equimolar testosterone. Complete suppression of oxytocin-induced LH se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…At this time, medium, oxytocin (100 n M ) [5]or NPY (1 µ M ) [4], alone or in combination, were perifused for 2 h. Samples of 20 min in duration were collected for measurement of LH by radioimmunoassay. For the study of tissue stimulated with GnRH, after the 2-hour pre-exposure, a 4-min pulse of GnRH (10 n M ) was delivered and delivery of oxytocin and/or NPY continued as in the prior treatment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At this time, medium, oxytocin (100 n M ) [5]or NPY (1 µ M ) [4], alone or in combination, were perifused for 2 h. Samples of 20 min in duration were collected for measurement of LH by radioimmunoassay. For the study of tissue stimulated with GnRH, after the 2-hour pre-exposure, a 4-min pulse of GnRH (10 n M ) was delivered and delivery of oxytocin and/or NPY continued as in the prior treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Oxytocin has been demonstrated to increase the secretion of LH from pituitary cells in static culture [5, 6], but there are no reports of its effects in dynamic perifusion conditions. The situation with regard to the direct action of NPY on gonadotropes is controversial.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that oxytocin increases release of LH from dispersed anterior pituitary cells [17, 33]and from tissue pieces [34], and thus effects on stores may have taken place. This study noted that oxytocin stimulated c-fos and LH expression within cells as detected by immunocytochemistry.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other investigations have revealed that peptides act at the pituitary to directly elicit LH release and/or to alter the effect of GnRH on the level of LH release [13]. It is believed that the steroidal milieu of the pituitary also has a significant effect on peptide activity [13, 14]. …”
Section: Introductionmentioning
confidence: 99%